A relevância da fundamentação para formação e aplicação dos precedentes - Fagundes, Cristiane Druve Tavares (2018)
The purpose of this present study is the analysis of precedents in the light of Brazilian Civil Procedure Code of 2015 and its close relation to judicial reasoning. The approach of this topic begins by the analysis of the classic division between civil law and common law, as well the approximation between them. Immediately thereafter, precedent classic standard and the main aspects that identify it are covered. Thirdly, the analysis goes to the Brazilian precedent standard according to the provision of Brazilian Civil Procedure Code of 2015. The authoress prefers to discuss the main issues through problems debated by doctrine and jurisprudence about that standard. In chapter 4, the topic examines the judicial reasoning as seen by Civil Procedure Code of 2015, focusing on its relevance as an element of intern validity of judicial decisions and outside of the process that they are given as well. In the end, the authoress joins the study of judicial reasoning relevance to the formation and the application of judicial precedents. The study is focused on the binding precedents, with the analysis of the traces of the Brazilian standard and the tools given by Civil Procedure Code to optimize the binding elements of the system. For the accomplishment of this study, the analysis of Brazilian authors is joined to that of foreigners, in a way to seek the most upgraded information on this matter. Therefore the aim of this study is a systematization of the concerning matter to the relevance of judicial reasoning for the formation and application of judicial precedents